Pengaruh Profitabilitas, Firm Size dan Sales Growth terhadap Tax Avoidance - Vallerie Redyna Putri; Mira Falatifah; Lady Karlinah (Politeknik Ganesha Medan, 2025)
Taxation plays a crucial role as one of the main sources of Indonesia’s revenue. However, taxpayers often attempt to avoid it through tax avoidance practices that exploit gaps or loopholes in tax regulations. This study aims to analyze the effect of profitability, firm size, and sales growth on tax avoidance. The sampling method used is purposive sampling, with a sample of 31 manufacturing companies in the food and beverage sub-sector from 2020 to 2022, obtained from secondary data on the Indonesia Stock Exchange website. The results of this study indicate that, partially, profitability has a significant negative effect on tax avoidance, firm size has a significant positive effect on tax avoidance, and sales growth has an insignificant negative effect on tax avoidance. Meanwhile, simultaneously, all three independent variables have an effect on tax avoidance. Keywords: Profitability, Firm Size, Sales Growth, Tax Avoidance